2010
DOI: 10.4065/mcp.2010.0113
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Analysis of Withdrawing Ventricular Assist Device Support

Abstract: OBJECTIVE: To describe a series of patients with heart failure supported with a ventricular assist device (VAD) who requested (or whose surrogates requested) withdrawal of VAD support and the legal and ethical aspects pertaining to these requests. PATIENTS AND METHODS:We retrospectively reviewed the medical records of patients at Mayo Clinic, Rochester, MN, from March 1, 2003, through January 31, 2009, who requested (or whose surrogates requested) withdrawal of VAD support and for whom the requests were fulfil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
107
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 22 publications
5
107
0
2
Order By: Relevance
“…12 When major medical procedures are initiated, there should always be some discussion of when they will be stopped. 13,14 Patients, family, and friends who know that a left ventricular assist device is a destination therapy and that the destination is a grim one or that dialysis when started and helpful will possibly be stopped at some point before death are far more likely to accept the limits of medicine than those who see a technologic treatment started without any mention that it may well be stopped.…”
mentioning
confidence: 99%
“…12 When major medical procedures are initiated, there should always be some discussion of when they will be stopped. 13,14 Patients, family, and friends who know that a left ventricular assist device is a destination therapy and that the destination is a grim one or that dialysis when started and helpful will possibly be stopped at some point before death are far more likely to accept the limits of medicine than those who see a technologic treatment started without any mention that it may well be stopped.…”
mentioning
confidence: 99%
“…Nevertheless, during our first year, 13 (68%) of 19 received PM consultation, which is an improvement compared with our prior experience of 0 of 36 patients receiving proactive PM consultation. 21 Before this endeavor, only 5 (14%) of 36 DT patients received PM consultation at any point in their care. 21 This finding is despite the fact that half of these 36 patients had died since the first implantation, with a median survival of 172 days (range, 1-1030 days) for all deceased DT patients at our institution from March 2003 to January 2009.…”
Section: Discussionmentioning
confidence: 99%
“…18 Also, protocols and processes regarding LVAD management and comfort at the end of life are often lacking 7,17 ; hence, ethical quandaries (eg, withdrawal of device support) may arise. 19,20 To avoid situations in which advance care wishes are unclear or unknown, palliative medicine (PM) consultation has been suggested 8,17,[21][22][23] to address end-of-life preferences, facilitate advance care planning, manage symptoms, and maximize QOL. Several authors have called for PM involvement in patients with advanced heart disease to improve health status and QOL, [24][25][26][27][28][29] and a recent randomized study of early palliative care vs standard care in advanced lung cancer has demonstrated improved QOL, improved mood, and survival benefit.…”
Section: Methodsmentioning
confidence: 99%
“…As VAD placement is discussed with patient and family, end of life issues must be addressed, not only because of the seriousness of the current illness and the potential mortality of the operation but also because the treatment equates to mobile life support [52 • ]. While VADs have repeatedly been shown to increase quality of life, the possibility of a patient eventually asking to withdraw this life-prolonging care has been seen in multiple studies to be approximately 20 % [51,53]. While some believe that once implanted a VAD becomes one with the patient and deactivating it amounts to euthanasia, most ethicists agree that deactivation of the VAD equates to withdrawal of life support and the terminal insult is that of heart failure, not the deactivation of the VAD by the physician [54].…”
Section: Ethical Concernsmentioning
confidence: 99%
“…As the medical community continues to develop life-saving technology, ethical dilemmas frequently arise, and VADs are rarely considered in advanced directives [51]. As VAD placement is discussed with patient and family, end of life issues must be addressed, not only because of the seriousness of the current illness and the potential mortality of the operation but also because the treatment equates to mobile life support [52 • ].…”
Section: Ethical Concernsmentioning
confidence: 99%